A Philosophical Perspective of Hermeneutics Study of Lived Experience of University Students with Self-Harm - Tumanggor, Roxsana Devi; Kongsuwan, Waraporn (Talenta Publisher, 2025)
Self-harm is a phenomenon characterized by the intentional infliction of injury or pain on the body, often without suicidal intent. Despite its prevalence, studies on this phenomenon within the Indonesian context remains limited, particularly in terms of the role of peer support. Therefore, this study aims to investigate the lived experience of university students who engage in self-harm and the perspectives of their supportive peers using hermeneutics phenomenological approach, rooted in the philosophy of Hans-Georg Gadamer. The complexity, sensitivity, and profoundly personal nature of self-harm was also explored using ontological, epistemological, axiological, and methodological foundations of hermeneutics. The strength of hermeneutics inquiry to explain meaning and context was assessed by a review of pertinent studies. The results identified several obstacles associated with ethical considerations and participants engagement. This shows that future nursing studies must focus on the development of nursing theories specific to self-harm, the integration of spiritual and religious perspectives, and culturally sensitive interventions. In addition, the current study validates the significance of hermeneutics in the advancement of nursing knowledge and practice in the context of mental health issues among young adults.